Pengaruh Sistem Informasi Akuntansi, Efektivitas Pengendalian Internal Terhadap Laporan Keuangan - Agustin, Adinda Virga; Wardatul Afiqoh, Nyimas (Journal of Culture Accounting and Auditing, 2025)
This study examines the effect of Accounting Information Systems (AIS) and Internal Control effectiveness on the Quality of Financial Statements. Using a quantitative approach, data were collected through questionnaires from 98 employees of PT Petrokopindo Cipta Selaras who use the Enterprise Resource Planning (ERP) system. The analysis, conducted with SmartPLS 4.0, shows that AIS has no significant effect on financial statement quality, while ERP implementation and effective internal control have positive and significant effects. Together, these variables enhance the reliability, accuracy, and transparency of financial reporting. The findings support the Resource-Based View and Agency Theory, emphasizing that the integration of technology and internal control systems improves the credibility of financial information